2016
DOI: 10.1038/srep34474
|View full text |Cite|
|
Sign up to set email alerts
|

Hexagonal Boron Nitride Tunnel Barriers Grown on Graphite by High Temperature Molecular Beam Epitaxy

Abstract: We demonstrate direct epitaxial growth of high-quality hexagonal boron nitride (hBN) layers on graphite using high-temperature plasma-assisted molecular beam epitaxy. Atomic force microscopy reveals mono- and few-layer island growth, while conducting atomic force microscopy shows that the grown hBN has a resistance which increases exponentially with the number of layers, and has electrical properties comparable to exfoliated hBN. X-ray photoelectron spectroscopy, Raman microscopy and spectroscopic ellipsometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
85
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 47 publications
11
85
0
1
Order By: Relevance
“…No studies on thickness determination of mono-or few-layer hBN by ellipsometry exist to our best knowledge, except for a brief mention with limited experimental details. 25 In this work, we first identify the key steps in the sample preparation phase and in the data analysis phase that are necessary in order to obtain reliable results from ellipsometry measurements on 2D hBN. Then, we demonstrate the ability of the ellipsometry technique to map the thickness and continuity of CVD-grown hBN down to monolayer thickness over regions of about 1 cm 2 , which can in principle be extended to any arbitrary area.…”
Section: Introductionmentioning
confidence: 99%
“…No studies on thickness determination of mono-or few-layer hBN by ellipsometry exist to our best knowledge, except for a brief mention with limited experimental details. 25 In this work, we first identify the key steps in the sample preparation phase and in the data analysis phase that are necessary in order to obtain reliable results from ellipsometry measurements on 2D hBN. Then, we demonstrate the ability of the ellipsometry technique to map the thickness and continuity of CVD-grown hBN down to monolayer thickness over regions of about 1 cm 2 , which can in principle be extended to any arbitrary area.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the topmost layer is free of defects, one might expect that the reaction terminates after total conversion of the first layer, or proceeds layer by layer. This in itself could be a useful approach for producing large area h‐BN layers on top of graphene, and may be useful as a 2D gate dielectric, tunnel barrier, or for encapsulation of epitaxial graphene devices . Furthermore, based on the higher chemical reactivity of monolayer graphene on SiC, due to the influence of the buffer layer, we speculate that the substitution reaction proceeds faster on graphene monolayers compared to multilayers.…”
mentioning
confidence: 97%
“…It is also attracting much attention as a wide band gap semiconductor material for deep-ultraviolet (DUV) applications [ 4 , 5 , 6 ]. There are now attempts world-wide to develop a reproducible technology for the epitaxial growth of large area high-quality hBN layers by chemical vapour deposition (CVD) [ 7 , 8 , 9 ], metal-organic chemical vapor deposition (MOCVD) [ 4 , 5 , 10 , 11 ], and molecular beam epitaxy (MBE) [ 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated high-temperature (HT) plasma-assisted MBE (PA-MBE) of hBN layers on both sapphire and highly oriented pyrolytic graphite (HOPG) substrates [ 22 , 26 , 28 ]. Our results demonstrated that by growing hBN using PA-MBE at HOPG substrate temperatures of ~1400 °C it is possible to produce monolayer and/or few-layer thick boron nitride with atomically flat hBN surfaces, which are essential for future applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation